Overview of Various Treatment Approaches and Their Impact on Several Difficult-to-Treat Conditions - S.M. Edelson (Moscow State University of Psychology and Education, 2020)
Several therapeutic approaches including medical, nutritional, sensory, and behavioral are reported to be effective in treating debilitating conditions often associated with autism. An overview of these approaches is discussed within the context of three difficult-to-treat conditions including anxiety, self-harming behavior, and sleep disturbances.